THE EFFICIENT MACHINES OF HUMAN BODIES: THE CIRCULATORY AND RESPIRATORY SYSTEMS (World Bulletin of Public Health, 2022)
The main focus of this article is to provide information related to the heart and lungs, with a special emphasis on clarification the significance of the “efficient machines” in the bodies of human beings. Moreover, it finds out the disorders that, with a higher probability, make the heart and lungs to function inappropriately, and shows the ways to develop healthy circulatory and respiratory systems
Keywords: high blood pressure; stroke; coronary heart disease; pneumonia